Socio-Psycholinguistic Implications of Rumour and Economic Hardship Among Bali Resident in Nigeria - Ali Kadiri, Abubakar; Aliyu, Bamanga; Sunday Achor, Salifu (International Journal of Language and Literary Studies, 2025)
Rumour has long been recognized as an influential factor shaping societal perceptions and behaviours. It often extends to economic activities. This paper examines the effect of rumours and economic hardship on residents of Bali, Taraba State, Nigeria. The focus is on the online media landscape. The objectives are to investigate the socio-psycholinguistic effects of rumour on foodstuff scarcity on Facebook; assess the responses of individuals on the new language that emerged from rumour about food scarcity; and explore the use of rumour to create artificial scarcity, which raises food prices. The study uses primary data from observation and online media documentation. The documents are analysed to understand how language is used in different social contexts. The Social Construction of Reality Theory and the Spreading Activation Theory are adopted to guide the study. The analysis of online media sources shows that rumour spreads quickly and influences the behaviour of local residents. As major findings, residents suffer from sociolinguistic and psycholinguistic effects of rumour due to the hardships caused by foodstuff scarcity. New language for food items is also found. Marketers use rumours to create artificial scarcity, leading to higher prices. These have accomplished the objectives of this study. Recommendations are made in line with the findings.